EVALUASI NERACA MASSA TOTAL DESAIN DAN AKTUAL DI WATER TRATMENT PLANT (WTP) PT. X - Franklin Sahuburua; Indar Putria; Firmanullah Fadlil; Ainul Alim Rahman (Universitas Pendidikan Muhammadiyah Sorong, 2025)
ABSTRACT The utilities unit, particularly the Water Treatment Plant (WTP), plays an important role in supporting the crude oil processing at PT. X. The performance of this unit can be evaluated through a mass balance calculation, which ensures that the quantity of materials entering, accumulating, and leaving the system is in accordance with the law of conservation of mass. This study aims to calculate and compare the total design and actual mass balance values to assess operational efficiency. The results indicate a discrepancy of 51.56 m³/h between the design and actual values, as well as a 10.83 m³/h difference between actual input and output values. These findings highlight the importance of intensive monitoring and control of operational parameters to minimize losses and optimize the performance of the utilities unit at PT. X.